2001
DOI: 10.2337/diabetes.50.3.614
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Scan for Abdominal Fat Assessed by Computed Tomography in the Québec Family Study

Abstract: To identify chromosomal regions harboring genes influencing the propensity to store fat in the abdominal area, a genome-wide scan for abdominal fat was performed in the Qué bec Family Study. Cross-sectional areas of the amount of abdominal total fat (ATF) and abdominal visceral fat (AVF) were assessed from a computed tomography scan taken at L4-L5 in 521 adult subjects. Abdominal subcutaneous fat (ASF) was obtained by computing the difference between ATF and AVF. The abdominal fat phenotypes were adjusted for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
100
0
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(111 citation statements)
references
References 38 publications
8
100
0
3
Order By: Relevance
“…In our study, the marker that demonstrated the strongest evidence for linkage coincides with a region reported by Perusse et al, 67 Genome scan of body fatness: HyperGEN CE Lewis et al subcutaneous fat in participants of the Quebec Family Study (Table 5). Two plausible candidate genes are located in the 17 cM (1 LOD unit drop) support interval, scavenger receptor type B class 1 (SRB1) and acetyl-CoA carboxylase-beta (ACACB).…”
Section: Discussionsupporting
confidence: 82%
“…In our study, the marker that demonstrated the strongest evidence for linkage coincides with a region reported by Perusse et al, 67 Genome scan of body fatness: HyperGEN CE Lewis et al subcutaneous fat in participants of the Quebec Family Study (Table 5). Two plausible candidate genes are located in the 17 cM (1 LOD unit drop) support interval, scavenger receptor type B class 1 (SRB1) and acetyl-CoA carboxylase-beta (ACACB).…”
Section: Discussionsupporting
confidence: 82%
“…Only two additional studies have conducted linkage analyses for such sophisticated measurements of adiposity, one in a French Caucasian population and one in an African-American and Caucasian population, 28,29 To our knowledge, no linkage studies in Hispanic populations have been carried out using CT measures of obesity. Thus, the IRASFS contributes novel data on linkage for specific fat depots in a Hispanic cohort.…”
Section: Discussionmentioning
confidence: 99%
“…29 Linkage was identified with markers D17S2180 (67cM), D17S1290 (82cM), and D17S1301 (100 cM), all with a LOD ¼ 2.2. 29 D17S1290 and D17S1301 were also genotyped in the IRASFS, with LOD scores for VAT ¼ 0.53 and 2.84, respectively, and LOD scores for BMI ¼ 1.01 and 2.11, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…There is suggestive evidence of linkage of abdominal subcutaneous fat to the chromosomal region 17q21.1 (LOD= 2.24), which is in close proximity to where both the PYY and PPY genes are located [26].…”
Section: Introductionmentioning
confidence: 99%